PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. KOTAK INDAH MAKMUR MEDAN - Wijaya, Albert (Aksara Public, 2019)
This study aims to test and analyze leadership and job satisfaction on the performance of employees of PT. Kotak Indah Makmur Medan. The method used is multiple linear regression analysis. The population is 90 people. The sampling technique uses a saturated sample, so that the total population is sampled. The results of this study found that partially leadership variables did not significantly influence employee performance. And job satisfaction variables significantly influence employee performance and simultaneous leadership and job satisfaction have a positive and significant effect on the performance of employees of PT. Kotak Indah Makmur Medan.